(untitled) (Research, Society and Development, 2022)
Wrist circumference has been shown to be a promising anthropometric measure and may be associated with comorbidities, such as hypertension, insulin resistance and cardiovascular diseases. Objective of the study was evaluate the association between wrist circumference (CPU) and body mass index (BMI), arm circumference (AC) and calf circumference (PC) and to aggregate the NFC as an indicator of nutritional status in patients with heart disease admitted to hospital. an ICU. A cross-sectional, descriptive study with an approach to the population of patients with heart disease in an ICU located in the Recôncavo region of Bahia. In the first 72 hours of admission, the following anthropometric assessments were performed: knee height (KA) followed by height estimation; BC followed by estimation of body mass and BMI; CP; CPU followed by the calculation of body complexion (CC). To establish the correlation between WC and AC, HC and BMI, Pearson’s correlation coefficients were used, considering the value of P<0.05. Description of the evaluated group: 22 men, 62.41±13.72 years, height (1.64±0.06 m), estimated body mass (63.63±16.72 kg), WC (34.84±6 .64 cm), CPU (18.08±0.97 cm), WC (9.13±0.52) and BMI (23.49±5.69 kg/m2). Regarding correlations: BMI vs. CB (r: 0.9815, P: 0.0001), BMI vs. CP (r: 0.5249, P: 0.0001), BMI vs. CC (r: 0.2956, P: 0.0089), CC vs. CB (r: 0.2483, P: 0.0183) and CC vs. CP (r: 0.1347, P: 0.0930). The NFC proved to be a simple and practical measure, with viable applicability that can be used in patients with heart disease admitted to the ICU.